2016
DOI: 10.18632/oncotarget.9419
|View full text |Cite
|
Sign up to set email alerts
|

Sialic acid removal from dendritic cells improves antigen cross-presentation and boosts anti-tumor immune responses

Abstract: Dendritic cells (DCs) hold promise for anti-cancer immunotherapy. However, clinically, their efficiency is limited and novel strategies to improve DC-mediated anti-tumor responses are needed. Human DCs display high content of sialic acids, which inhibits their maturation and co-stimulation capacity. Here, we aimed to understand whether exogenous desialylation of DCs improves their anti-tumor immunity. Compared to fully sialylated DCs, desialylated human DCs loaded with tumor-antigens showed enhanced ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 40 publications
(48 reference statements)
5
39
0
Order By: Relevance
“…Several groups have reported that removal of surface sialic acids with bacterial sialidases enhanced the response of DCs to LPS. In addition to enhanced maturation and cytokine production upon LPS stimulation, DCs treated with sialidase were also more potent T‐cell activators 8 , 9 , 10 , 11 , 12 , 13 , 14 . These data evidence that sialic acids limit the response of DCs to stimulation via the TLR pathway.…”
Section: Introductionmentioning
confidence: 78%
“…Several groups have reported that removal of surface sialic acids with bacterial sialidases enhanced the response of DCs to LPS. In addition to enhanced maturation and cytokine production upon LPS stimulation, DCs treated with sialidase were also more potent T‐cell activators 8 , 9 , 10 , 11 , 12 , 13 , 14 . These data evidence that sialic acids limit the response of DCs to stimulation via the TLR pathway.…”
Section: Introductionmentioning
confidence: 78%
“…Desialylated DCs have higher expression of MHC-I, MHC-II and co-stimulatory molecules (e.g., CD80, CD86), and higher secretion of pro-inflammatory cytokines, which altogether contribute to a superior T H 1 anti-tumoral response. ST6Gal-I knockout DCs also show increased capacity to activate T cells, further supporting that the ability of DCs to induce T H 1 anti-tumoral responses is improved by sialic acid removal [16,17]. Initially thought as mere induction of DC maturation [16] the fact is that the molecular mechanisms behind this outcome are still poorly characterized.…”
Section: Introductionmentioning
confidence: 86%
“…The levels of sialic acid at DCs surface were shown to modulate the maturation status of both murine and human DCs [16]. Previous results from our group showed that the temporary removal of surface sialic acids by sialidase treatment increased the ability of human monocyte-derived DCs to activate T cells and to provide antigen-specific anti-tumoral responses [17]. Desialylated DCs have higher expression of MHC-I, MHC-II and co-stimulatory molecules (e.g., CD80, CD86), and higher secretion of pro-inflammatory cytokines, which altogether contribute to a superior T H 1 anti-tumoral response.…”
Section: Introductionmentioning
confidence: 96%
“…This implies a distinct possibility that malignancy-induced changes in platelet homeostasis and activation can contribute to the overall tumor microenvironment whereby extrinsic remodeling of cell surface glycans alters the host antitumor response. Indeed, removal of sialic acids from immune cell surfaces such as dendritic cells results in their enhanced ability for anti-tumor activity (Silva et al 2016). By inference then, excessive sialylation, triggered by platelet activation, should impose a dampening of normal immune cell functions, leading to poorer outcomes in malignancies with thrombocytosis.…”
Section: Discussionmentioning
confidence: 99%